EFEKTIFITAS MEDIA PEMBELAJARAN PANTOMIM UNTUK MENINGKATKAN KEMAHIRAN BERBICARA (MAHARAH KALAM) - Eko Budi Hartanto (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
This research is motivated by the difficulties of MTs students. Sunan Bonang Sarang-Rembang both in speaking and making Arabic conversation texts. So this research was carried out using pantomime media to improve students' speaking ability in Arabic, it aims to find out how the application of pantomime, what are the challenges and how to overcome them, and whether there are differences in the ability of students before and after pantomime. This study uses quantitative research and the target is students of class IX MTs. Sunan Bonang Sarang, Rembang. And to find out the results of the problem formulation, the authors use several data collection methods, including interviews, documentation, questionnaires, tests, and observations. The data analysis technique used in this study is parametric statistical analysis with the t test formula. By using the data collection method, it can be concluded that there is an influence between before applying the pantomime game and after applying the pantomime game, it can be seen from the percentage of student questionnaires stating 75.31% they agree and support the application of this game, they also think that they are easier and more confident when speaking and making muhadatsah texts after playing pantomime. The influence of the application of this pantomime game is very strong seen from the correlation result which is 0.95. As for the t test results from the application of this game is 5.482, when compared with t tables with a significant level of 0.05% which is worth 2,000. Then t count > t table. This means that Ha is accepted and Ho is rejected, or there is an increase in students' ability to speak Arabic between before and after the implementation of the mime game.